Effects of addition of Magnesium sulphate to heavy Bupivacaine for spinal anesthesia in vaginal hysterectomy - Tabdar, Sushila; Shrestha, Uzma; Kadariya, Ekraj (Journal of Kathmandu Medical College, 2014)
Background: Adequate pain management is essential for every patient to recover and return to their normal activity quickly. Central sensitization is one of the mechanism which increases excitability of spinal neurons and results persistent pain postoperatively. Objectives: The aim of the study was to investigate the effects of addition of 100 mg 50% Magnesium Sulphate intrathecally to 0.5% heavy Bupivacaine on sensory onset up to T4 level, complete motor block, post-operative analgesia and complications in patients planned for vaginal hysterectomy under spinal anesthesia. Methods: The design of the study was prospective randomized and double blind. With the Institutional improvements and informed consent in Kathmandu Medical College from January 2011 till December 2012, 60 American society of Anesthesiologist class (I, II) patients of age between (40 to 70) years, weight between (45 to 70) kg and height between (4.8 to 5.2) feet undergoing routine vaginal hysterectomy not exceeding one and half hour in spinal anaesthesia were included in the study. The exclusion criteria were patients not following above criteria, having coagulopathy, renal function derangements, uncontrolled hypertension or severe hypotension and having dysarrhythmias. Total patients were randomized into two groups of thirty each. Group A was allocated to receive four ml 0.5% Bupivacaine +0.25 ml normal saline and group B was allocated to receive four ml 0.5% Bupivacaine + 100 mg of 50% Magnesium Sulphate. The anaesthesiologist who was double blind to the drug preparation performed spinal anaesthesia with either of the drug for the whole study.The recorded parameters were time of onset of sensory block upto T4 level, onset of complete motor block, total duration of analgesia and complications in both the groups. Data analysis was done by Computer software polystat XLS using Student’s “t” test. P value <0.05 was considered statistically significant. Result: The addition of 100 mg of 50% Magnesium sulphate to 0.5% Bupivacaine intrathecally resulted early onset of sensory block upto T4 level in (Mean± SD) (3.79 ± 0.25) min Vs (9.61 ± 0.75) min with sole 0.5% Bupivacaine where p value was < 0.05. Similarly onset of complete motor block with 0.5% Bupivacaine plus Magnesium Sulphate was (1.9 ± 0.23) min verses (10.4 ± 0.63) min with 0.5 % Bupivacaine only. Here again p value was < 0.05. Duration of analgesia with 0.5 % Bupivacaine plus Magnesium Sulphate was (176.8 ± 19. 85) min than that of 0.5% Bupivacaine (105 ± 26.82) min with P value< 0.05. Conclusion: The study concluded that onset as well as analgesic effect of 0.5% Bupivacaine was potentiated by intrathecal Magnesium Sulphate without major side effects. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10628 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, Page: 63-68